Investigations into the dyeing industry in Pompeii : experimental archaeology and computer simulation techniques - Pepper, Heather Hopkins, (Archaeopress Roman archaeology ;, 2022)
The scale of processing associated with the dyeing industry in Pompeii is a controversial subject. To determine the scale of manufacturing would allow an understanding of the operation of Pompeii's economy and its part in the Roman World. Previous studies have taken a theoretical approach, and no conclusive answer has been reached. Conversely, this book uses a new multi-disciplinary triangulated approach. A replica was constructed to gauge the operating parameters of a dyeing apparatus within the framework of the principles of experimental archaeology. The remains were re-examined in situ with the new operational and ergonomics understanding. The replica was amended to allow exploration of design features and ventilation. The throughput of the apparatus was placed within the context of the industry with modern manufacturing systems theory.